2020
DOI: 10.3389/fneur.2020.577874
|View full text |Cite
|
Sign up to set email alerts
|

Association Between REM Sleep Behavior Disorder and Cognitive Dysfunctions in Parkinson's Disease: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Rapid eye movement sleep behavior disorder (RBD) is thought to be a prodromal symptom of Parkinson's disease (PD). RBD is also thought to be involved in cognitive decline and dementia in PD. In PD, although the relationship between RBD and cognitive dysfunctions was confirmed by considerable studies, whether RBD was associated with distinct types of cognitive defects is worth of study. Objectives: This systematic review summarizes the evidence relating to cognitive dysfunction in PD patients with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 165 publications
(231 reference statements)
1
10
1
Order By: Relevance
“…Although we assessed RBD via a screening questionnaire, our results were consistent with a prior study using PSG-proven RBD, which indicated an association of a non-motor dominant phenotype in PD with PSG-proven RBD [ 4 ]. However, we observed only a trend in the negative effect of pRBD on global cognitive performance in PD, which did not correspond to several cross-sectional and longitudinal studies [ 8 ]. To assess a potential independent variable influencing cognitive performance, we identified a protective effect of YoE on cognitive decline in the overall PD group, but we did not identify a significant difference in pRBD PD vs. non-pRBD PD in terms of YoE or TLS.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although we assessed RBD via a screening questionnaire, our results were consistent with a prior study using PSG-proven RBD, which indicated an association of a non-motor dominant phenotype in PD with PSG-proven RBD [ 4 ]. However, we observed only a trend in the negative effect of pRBD on global cognitive performance in PD, which did not correspond to several cross-sectional and longitudinal studies [ 8 ]. To assess a potential independent variable influencing cognitive performance, we identified a protective effect of YoE on cognitive decline in the overall PD group, but we did not identify a significant difference in pRBD PD vs. non-pRBD PD in terms of YoE or TLS.…”
Section: Discussioncontrasting
confidence: 99%
“…sectional and longitudinal studies[8]. To assess a269 potential independent variable influencing cognitive 270 performance, we identified a protective effect of YoE 271 on cognitive decline in the overall PD group, but we 272 did not identify a significant difference in pRBD PD 273 vs. non-pRBD PD in terms of YoE or TLS.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…When combining the effects of age and the severity of extrapyramidal signs, risk of incident dementia in PD was significantly increased [ 26 ]. In addition to motor symptoms, we also found that one non-motor symptom, RBD, was closely related to MCI in PD, which was also in line with previous cross-sectional and longitudinal studies [ 28 ]. Natalia Jozwiak et al found that PD patients with RBD had poorer performance on cognitive tests measuring attention, executive functions, language, memory and visuospatial abilities [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, PD patients with co-existent RBD are characterized by older ages, male, younger ages of PD onset, akinetic/rigid phenotype, falls, higher disease severity, longer disease duration, greater motor fluctuations, and higher levodopa dose [ 21 , 103 ]. Meta-analysis also strongly suggests a relationship between RBD and cognitive impairment, making it a sign of worsening condition in PD patients [ 104 ].…”
Section: Sleep Disorders and Pharmacological Treatmentsmentioning
confidence: 99%